2002
DOI: 10.1038/sj/mp/4000949
|View full text |Cite
|
Sign up to set email alerts
|

Early experience and serotonin transporter gene variation interact to influence primate CNS function

Abstract: Nonhuman primates offer unique opportunities to study the effects of genes, environments, and their interaction, on physiology and complex behavior. We examined genotype and early environment contributions to CNS function in a large sample of rhesus monkeys. In humans, length variation of the serotonin (5-HT) transporter (5-HTT) gene-linked polymorphic region (5-HTTLPR) that results in allelic variation in 5-HTT expression is associated with decreased serotonergic function and 5-HT-mediated psychopathology. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 37 publications
6
148
0
4
Order By: Relevance
“…The causes of naturally occurring individual differences in serotonergic function, however, are not well understood. A previous study of rhesus monkeys found no significant variation in CSF 5-HIAA concentrations in relation to serotonin transporter gene polymorphism but reported that the individuals with the s allele were more vulnerable to the effects of early social deprivation on later neuroendocrine and behavioral responsiveness than the individuals with the l allele (Bennett et al, 2002). The sample size of our study was too small to permit investigation of a similar Genotype ϫ Environment interaction, but nevertheless, our results suggest that early interactions with the mother are an important source of developmental variation in monoaminergic function.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The causes of naturally occurring individual differences in serotonergic function, however, are not well understood. A previous study of rhesus monkeys found no significant variation in CSF 5-HIAA concentrations in relation to serotonin transporter gene polymorphism but reported that the individuals with the s allele were more vulnerable to the effects of early social deprivation on later neuroendocrine and behavioral responsiveness than the individuals with the l allele (Bennett et al, 2002). The sample size of our study was too small to permit investigation of a similar Genotype ϫ Environment interaction, but nevertheless, our results suggest that early interactions with the mother are an important source of developmental variation in monoaminergic function.…”
Section: Discussionmentioning
confidence: 90%
“…Some of these studies have shown that individual differences in vulnerability to adverse early experience are modulated by genetic factors, such as the polymorphism in the serotonin transporter gene. In rhesus monkeys, a 21-base pair insertion/deletion polymorphism analogous to the human 5-hydroxytryptamine transporter gene (5-HTT) length variant of the gene-linked polymorphic region (rh5-HTTLPR) has been found in the same transcriptional region, resulting in similar allelic variation and reductions in transcriptional efficiency (Bennett et al, 2002). Rhesus monkeys with the short (s) allele are more vulnerable to the developmental dysregulation of the HPA axis induced by early social deprivation than are monkeys with the long (l) allele (Barr, Newman, Lindell, et al, 2004;Bennett et al, 2002).…”
mentioning
confidence: 99%
“…82 In rhesus macaques, with an SERTLPR analogous to that of humans, the short allele is associated with decreased serotonergic function among monkeys reared in stressful conditions, but not among normally reared monkeys. 83 In humans, individuals with one or two copies of short allele of the SERT promoter polymorphism exhibited more depressive symptoms, diagnosable depression, and suicidality in relation to stressful life events than individuals homozygous for the long allele; however, no direct association between the SERT gene and depression was observed. 84 Taken together, these studies show that there may not be a direct relationship between SERTLPR and a variety of biochemical and clinical phenotypes; yet, intriguing results do imply a role for SERTLPR in behavioral disorders when environmental factors are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…9 The less active s-allele interacts with adverse early rearing conditions (peer rearing) to result in more distress, less activity, stronger neuroendocrine responses to stress, higher consumption of alcohol and lower serotonin turnover in the central nervous system. 8,9,26,27 During peerrearing, animals homozygous for the l allele develop more socially acceptable playful behaviours but sl heterozygotes tend to become aggressive, suggesting that the ll homozygous status confers an adaptive potential for adverse environment. 28 In conclusion, the non-human primate experiments support the G Â E hypothesis by showing that the s allele is associated with a vulnerability to early life adverse circumstances leading to multiple adverse outcomes resembling human psychiatric disorders.…”
Section: Animal Modelsmentioning
confidence: 99%
“…2,3 Quantitative human population genetics studies indicate that G Â E plays a role in the development of depression. [4][5][6][7] In the last five years, G Â E involving specific gene polymorphisms has been identified in animals 8,9 and humans. [10][11][12][13] Encouragingly, replications 14,15 and a positive metaanalysis 16 indicate that measuring environment improves the reliability of genetic research.…”
Section: Introductionmentioning
confidence: 99%